An Automated Optimize Utilization of Water and Crop Monitoring in Agriculture Using IoT. Issue 1 (April 2021) - Dogiwal, Sanwta Ram; Dadheech, Pankaj; Kumar, Ankit; Raja, Linesh; Kumar, Abhishek; Kumar Beniwal, Mahender
Abstract: AI Solution for Farmers is an agricultural based project, created to help farmers and to help them in increasing their productivity. Since the technologies are running the world, why agriculture must be deprived of it. Agriculture is one of the most important areas that have major impacts on the economy and society of a country. Technological developments serve as tools to share knowledge and practices of agricultural products and make more satisfactory lives for farmers, traders, policymakers, and the overall society. It is evident that knowledge has become a crucial component in production, society, food security, health, poverty, and other millennium development goals. The use of technology may provide a better approach to solve the problems arising from sowing the seed to harvest the crop. The new technologies like Machine Learning and Data Science may be great help to have an eye on the deciding factors to the growth of crop.